A DESCRIPTION OF PERINATAL AS A RISK FACTOR OF CHILDREN’S SENSORINEURAL HEARING DISORDER IN OTOLARYNGOLOGY (ENT) POLYCLINIC OF ABDUL WAHAB HOSPITAL SJAHRANIE IN SAMARINDA - Inna Inna Adilah; Moriko Pratiningrum (Universitas Muhammadiyah Kalimantan Timur, 2020)
Sensorineural Hearing Disorder in children could give a significant impact on everyday life and would cause loneliness, isolation, and frustration on children. Perinatal risk factors are important to note because they could be detected from newborn and could be an indication for the baby to do the screening. The purpose of hearing screening in newborns is to find hearing loss as early as possible so that habilitation can be done immediately. The purpose of this study was to describe perinatal period as risk factors for Sensorineural Hearing Disorder in children. The subjects of this study were children who has done BERA examinations at the Otolaryngology (ENT) Polyclinic of Abdul Wahab Sjahranie Hospital in Samarinda from January 2017 – June 2019. The design of this study was observational descriptive with cross-sectional method. There were 65 children as sample which consisted of 39 (60%) boys and 26 (40%) girls. BERA examination age that was found in this study has not reached the optimal standard if it is referring to the JCIH standard with the most age group is 3 years old. 37 (56.9%) children suffered from Sensorineural Hearing Disorder. 27 (41.5%) children had perinatal risk factors. The most common risk factors was jaundice which the researchers found on 11 (16.9%) children. 20 (30.8%) children who have perinatal risk factors and Sensorineural Hearing Disorder with the most common risk factor is LBW are as many as 10 (15.4%).